Study of Moisture Impact on Asphalt Before and After Oxidation Using Molecular Dynamics Simulations. Issue 1 (2016) - Pan, Jielin; Tarefder, Rafiqul A.; Hossain, Mohammad I.
Moisture effects on asphalt before and after oxidative aging are investigated in this paper with the molecular dynamics (MD) simulation method. Density, bulk modulus, and zero shear viscosity changes of unoxidized and oxidized asphalt under different moisture contents are compared. The simulations were conducted at 25°C with 0% and 1%, to 10% moisture inclusion incremented by 2.5%. Simulation results showed that the density, bulk modulus, and zero shear viscosity of oxidized asphalt were higher than those of the unoxidized asphalt before any moisture inclusion. These results indicate that hardening happens in asphalt during oxidation. However, after moisture inclusion, the bulk modulus and the zero shear viscosity of unoxidized and oxidized asphalt decreased with an increase in moisture content. Laboratory validation of zero shear viscosity for the unoxidized asphalt showed a result consistent with MD simulation. The moisture effect on density change was not significant for unoxidized or oxidized asphalt, but the density fluctuations of oxidized asphalt were higher than for the unoxidized asphalt. Moreover, moisture affects the bulk modulus and zero shear viscosity of oxidized asphalt more negatively, compared with the unoxidized asphalt. Specifically, the bulk modulus and zero shear viscosity of oxidized asphalt decreased faster than the unoxidized asphalt with moisture inclusion and became lower than the unoxidized asphalt after 5% moisture inclusion. This result indicates that oxidized asphalt is more susceptible to moisture damage.